PENGGUNAAN PERALATAN RADIATION PORTAL MONITOR DALAM RANGKA MENDUKUNG KEAMANAN NUKLIR NASIONAL - Hermawan, Nanang Triagung Edi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
The issue of security is a very serious concern of the world community after the bombing of the World Trade Center in the United States on September 11, 2001. Threat of terrorism will be more dangerous if they use radioactive or nuclear material in the form of radiological dispersal devices (RDDs). RDDs also known dirty bomb. Dirty bomb is a conventional bomb mixed with radioactive substances as impurity. In addition to the effects of power damaged by their explosive capabilities, dirty bombs also caused tremendous fear due to radioactive contamination. Any use of radioactive and nuclear materials should have the license from the competent regulatory body. Smuggling, illegal trafficking, and abuse of radioactive and nuclear materials must be prevented. The total area and form an archipelago country likes Indonesia have a vulnerability to smuggling of radioactive and nuclear materials from abroad. One of the tools that can be used for prevention of smuggling is Radiation Portal Monitor (RPM). RPM is a set of detector equipment for gamma and neutron radiation that can check a vehicle or cargo container without having to open the payload. RPM needs to be installed at any convenient border crossing points. By RPM, cargo inspection will run faster, more practical, and has a high accuracy. Keywords: security threat, radioactive material, nuclear material, dirty bomb, and RPM.